2020
DOI: 10.1039/c9cp05643b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of twin orbital-order phases in ferromagnetic semiconducting VI3 monolayer

Abstract: Discovery of twin orbital-order ferromagnetic semiconducting phases in VI3-like 2D systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…There is still some controversy regarding the MAE of VI 3 . 17,19,20,37,[40][41][42][43][44] By fitting the spin wave gap in the Raman spectrum, the MAE can be estimated as 2.32 meV per cell. 41 However, some MAE values with a large difference, such as 0.29 meV per cell and 31.8 meV per cell, have also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…There is still some controversy regarding the MAE of VI 3 . 17,19,20,37,[40][41][42][43][44] By fitting the spin wave gap in the Raman spectrum, the MAE can be estimated as 2.32 meV per cell. 41 However, some MAE values with a large difference, such as 0.29 meV per cell and 31.8 meV per cell, have also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, it has been demonstrated that a strain tuning can result in an enhancement of magnetic ordering temperature, or in switching of magnetic state from the ferromagnetic (FM) to an antiferromagnetic (AFM) half-semiconductor in CrI and VI monolayers and in their heterostructures 31 34 . Also, the Dirac half-metallicity and the twin orbital-order phases were predicted to exist in a monolayer of VI 24 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two-dimensional (2D) van der Waals transition metal MX 2 dihalides and trihalides MX 3 with X a halogen ligand have become of interest as they exhibit layer-dependent ferromagnetism as in VI 3 [27][28][29][30][31][32], possible Kitaev spin liquid behavior in RuCl 3 [33][34][35][36][37][38] and other magnetic phenomena [39][40][41]. Additionally, the crystal and electronic structures are highly two dimensional, so the materials can be exfoliated, made in monolayer form, doped by gating and layering with other compounds, and potentially twisted into Moiré materials [42].…”
Section: Introductionmentioning
confidence: 99%